Reductions in tonic GABAergic current in substantia gelatinosa neurons and GABAA receptor δ subunit expression after chronic constriction injury of the sciatic nerve in mice. (25th May 2016) - Iura, A.; Takahashi, A.; Hakata, S.; Mashimo, T.; Fujino, Y.
Abstract: Background: Decreased Gamma‐aminobutyric acid (GABA)‐ergic phasic inhibitory transmission in the spinal cord is thought to be responsible for the development of neuropathic pain. However, the role of GABAergic tonic current in substantia gelatinosa (SG) neurons in neuropathic pain remains to be fully elucidated. In this study, we assessed GABAergic tonic currents of SG neurons in a sciatic nerve chronic constriction injury (CCI) mouse. Method: Whole‐cell patch clamp recordings form lumbar spinal cord slices was performed to evaluate GABAergic currents. We also investigated the expression changes of GABAA receptor subunits which are considered to mediate tonic currents. Results: The percentage of SG neurons receiving GABAergic tonic currents decreased in CCI mice compared with Naïve mice. No significant change was observed in the mean amplitude of GABAergic tonic currents. RT‐PCR and Western blot revealed that the expression of GABAA receptor δ subunits decreased following CCI. Conclusion: A reduction in the expression the δ subunit of the GABAA receptor and diminished GABAergic tonic current in SG neurons were observed after CCI in mice. GABAergic tonic current plays a key role in neuropathic pain. The GABAA receptor δ subunit may be a therapeutic target in neuropathic pain. What does this study add?: In spinal SG neurons, GABAergic inhibitory transmission operates through both phasic and tonic currents, but physiological role is largely unknown. In this study, we report dysregulation of GABAA receptor δ subunit‐mediated tonic current in SG neurons may result in spinal disinhibition resulting in neuropathic pain in CCI mice.